Investigation into the Application of Construction and Demolition Waste in Urban Roads - Youyun Li; Hui Zhou; Linjian Su; Hang Hou; Li Dang (Advances in Materials Science and Engineering)
The recycling and reuse of waste materials is a topic of global concern and great international interest for those interested in sustainable development and protecting the environment. In recent decades, global production of construction and demolition waste (C&D waste) has significantly increased and became a worldwide problem. This research proposes to evaluate the feasibility of using aggregate from recycled C&D waste for urban road embankment applications based on the Sanhuan road construction project in eastern Xi’an. An extensive suite of laboratory and field compaction tests were carried out to determine the physical properties and engineering characteristics of the C&D waste. The effect of curing on the strength of the C&D waste was investigated using unconfined compression strength (UCS), California bearing ratio (CBR), and deflection tests. The results show that the C&D waste has the characteristics of high strength and significant stability after simple treatment and further suggest that the use of these materials for paving urban road embankments is feasible. This study is of value for the reasonable and effective promotion of using C&D waste recycled materials in road subgrade applications.